Locutionary, Illocutionary and Perlocutionary Acts in the Short Story â€œLetters from the Fatherâ€ by Mona Trisyah - Aulia Fitriyani; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
Speech acts are not only found in oral communication, but also in written form as in prose-shaped literary works, one of which is short stories. The structure of language and the structure of society influence each other. The emergence of linguistic units cannot be explained only by linguistic rules. There is a phenomenon which shows that one utterance can be used to express various kinds of speech acts. This research is a qualitative descriptive study. The description of the data is in the form of story excerpts and dialogue in the short story